Creative self-efficacy and social skills in a Portuguese sample of university students: Links with self-esteem, academic achievement and life satisfaction - González Moreno, A. (2024)
Creative self-efficacy and social skills are two elements that can significantly enhance personal and professional development. The main objective of this research is to analyze the relations established between creative self-efficacy and social skills with other variables such as self-esteem, academic performance, and life satisfaction. The participants included in the methodology of this study are a total of 238 Portuguese university students. The instruments used were the Creative Self-Efficacy Scale, the Social Skills Questionnaire (CHASO), the Rosenberg Self-Esteem Scale (RSES), the Satisfaction with Life Scale (SWLS), and a series of ad hoc questions to assess academic performance. The results obtained indicate the existence of significant relations between creative self-efficacy and social skills, with the latter also being positively associated with self-esteem and life satisfaction. Analyses indicate that there are significant differences according to gender, academic performance, and the level of self-esteem of the participants. In addition, variables such as self-esteem, academic performance, and fluency act as predictors of life satisfaction. The importance of further exploring and understanding the complex relationship between creative self-efficacy, social skills, and individual well-being in the university context is discussed.